Pro Kontra Ulama Tentang Munasabah Al-Qur’an - M Fatih (Pena Islam Jurnal Pendidikan Agama Islam, 2021)
Munasabah al-quran is a study of the relationship between the parts of the al-Qur'ān. Munāsabah is closely related to the issue of i'jāz, so that it is a special study of the al-Qur'ān text that is different from other texts. The text of the al-Qur'ān is a structural unit whose parts are interrelated. Therefore, in order to reveal these relationships, it is necessary to have the ability and sharpness of the views of the commentator in capturing the horizon of the text. Munāsabah is an intellectualization effort based on a meaning or rigging which is rationally considered to be able to connect parts of the al-Qur'ān. Some scholars argue that the munasabah al-Qur'an is something that is too forced, because the al-Qur'ān was sent down for more than twenty years regarding various laws for different reasons. This fact does not make it easy to relate to one another. Even if there is a linkage between all the parts of the Qur'an, then this linkage is weak and does not constitute a solid connection which is avoided by a quality utterance.